Idealny król mesjański (Iz 7,10-17; 8,23-9, 6; 11,1-9) / Gabriel Witaszek. - Witaszek, Gabriel (1951- ).
1. Znak Emmanuela (Iz 7,10-17). 2. Światło i radość (Iz 8,23-9, 6). 3. Różdżka Jessego (Iz 11,1-9).